أهمية التصوير الومضاني الطبقي 99mTc-HMPAO SPECT في كشف تبدلات التروية الدموية الدماغية في مرضى التوحد - شبيب, حمزة (Latakia University Journal -Medical Sciences Series, 2013)
أجري الفحص الومضاني الطبقي للدماغ 99mTc-HMPAO SPECT ل 22 طفلاً مصاباً بالتوحد والتخلف العقلي و ل 8 أطفال يعانون من التخلف العقلي كشاهد. تبين بنتيجة الفحص الومضاني الطبقي أن هناك نقص تروية دماغية مؤثراً في الفصوص الصدغية والمنطقة المهادية والنوى القاعدية للمتوحدين, مقارنة مع مجموعة الشاهد. تناسبت الأعراض السريرية للمتوحدين مع نقص التروية في المنطقة المهادية، ولم تتناسب مع نقص التروية في بقية المناطق. لم يثبت إحصائياً فروق مؤثرة بالنسبة لعمر المرضى، تقدير عمرهم العقلي، وزنهم، ومحيط رأسهم بين المتوحدين ومجموعة الشاهد، بينما كان هناك فروق إحصائية مؤثرة بين المتوحدين ومجموعة الشاهد بالنسبة لمقياس تقييم التوحد الطفولي، قائمة السلوك الشاذ التي تشمل الإثارة، البلادة، التكرارية، النشاط الزائد والإفراط في الكلام. أثبتت الدراسة فعالية المعالجة المناسبة في بعض المتوحدين الذين لديهم نقص تروية دماغية بدون وجود تبدلات بنيوية دماغية سواء بالتصوير الطبقي المحوري أو بالرنين المغناطيسي. 99mTc HMPAO single-photon emission computed tomography (SPECT) brain perfusion was conducted in 22 mentally retarded autistic individuals and 8 patients with mental retardation as control group. Autistic patients had significantly lower perfusion than control group in the following brain regions: temporal lobes, basal ganglia, and thalami. Signs and symptoms were correlated to decreased regional perfusion in the thalamic region, but no correlation between symptoms and decreased regional perfusion in the rest of the brain lobes. Statistically, no significant differences between autistic and control group for, age, assessment of mental age, weight and head circumference, while there were statistically significant differences between autistic patients and control group related to childhood autism rating scale, and aberrant behavior checklist (irritability, lethargy, stereotypic behaviors, hyperactivity and excessive speech). The study demonstrated the effectiveness of appropriate treatment in some autistic patients with brain hypoperfusion on 99mTc HMPAO-SPECT without detection of structural changes on CT or MRI.